2003
DOI: 10.1046/j.1365-2311.2003.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in egg cold hardiness: a study on the adaptation strategies of the migratory locust Locusta migratoria L.

Abstract: Abstract. 1. For many species of insect, cold hardiness is an important trait that enables a population to develop in the next season and to extend its range. To elucidate the role of cold hardiness of the migratory locust Locusta migratoria L. in its outbreak and distribution areas, egg cold hardiness was examined in locusts derived from four locations from latitude 18 23 0 N to latitude 41 10 0 N in eastern China.2. The supercooling points of eggs from different geographic populations did not differ signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 23 publications
2
55
2
2
Order By: Relevance
“…A maximum variation in SCPs of 10°C was observed between geographic populations of the leafminer pupae, which is a rare record for insects (Turnock et al, 1998;Shintani and Ishikawa, 1999;Klok et al, 2003;Chen and Kang, 2004). The northern populations are commonly more cold-tolerant than southern populations, so as to adapt to local environmental stress through evolutionary pathways or natural selection (Masaki, 1996;Jing and Kang, 2003;Chen and Kang, 2004;Kimura, 2004). For L. sativae, the southernmost population had the highest mean SCP value.…”
Section: Discussionmentioning
confidence: 99%
“…A maximum variation in SCPs of 10°C was observed between geographic populations of the leafminer pupae, which is a rare record for insects (Turnock et al, 1998;Shintani and Ishikawa, 1999;Klok et al, 2003;Chen and Kang, 2004). The northern populations are commonly more cold-tolerant than southern populations, so as to adapt to local environmental stress through evolutionary pathways or natural selection (Masaki, 1996;Jing and Kang, 2003;Chen and Kang, 2004;Kimura, 2004). For L. sativae, the southernmost population had the highest mean SCP value.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that populations at high latitude have higher cold resistances than at low latitude, and temperate species are more cold tolerant than subtropical or tropical species (Hoffmann et al 2003;Jing and Kang 2003;Kimura 2004). For the southern populations of L. sativae, the mean SCP of pupae was substantially depressed with decreasing latitude.…”
Section: Discussionmentioning
confidence: 95%
“…It corresponds to the onset of a sharp rebound on the thermal curve due to the release of the latent heat of ice crystallization. The SCPs of the individuals at different developmental stages were measured using the method described by Jing and Kang [8]. Numbers of assayed individuals of eggs, larvae, pupae and adults were 20, 100, 20 and 30, respectively.…”
Section: Measurement Of Supercooling Points (Scps)mentioning
confidence: 99%